A goal-based approach to engineering capacity-driven Web services. (21st March 2014) - Maamar, Zakaria; Tata, Samir; Yetongnon, Kokou; Benslimane, Djamal; Thiran, Philippe
Abstract This paper discusses a goal-based approach for the engineering of capacity-driven Web services. In this approach, goals are established to first, define the roles that these Web services will play in implementing business applications, second, frame the requirements that will be put on these Web services, and third, identify the processes in terms of business logics that these Web services will carry out. Because of the nature of capacity-driven Web services compared with regular (i.e. mono-capacity) Web services, their engineering in terms of design, development, and deployment takes place in a different way. A Web service that is empowered with several capacities, which are basically separate groups of operations to execute, has to choose one capacity for triggering at run-time. To this end, the Web service takes into account different types of requirements like data and privacy that are put on each capacity that empowers this Web service.